Measuring Ventilatory Activity with Structured Light Plethysmography (SLP) Reduces Instrumental Observer Effect and Preserves Tidal Breathing Variability in Healthy and COPD - Niérat, Marie-Cécile; Dubé, Bruno-Pierre; Llontop, Claudia; Bellocq, Agnès; Layachi Ben Mohamed, Lila; Rivals, Isabelle; Straus, Christian; Similowski, Thomas; Laveneziana, Pierantonio (Frontiers in Physiology, 2017)
The use of a mouthpiece to measure ventilatory flow with a pneumotachograph (PNT) introduces a major perturbation to breathing (“instrumental/observer effect”) and suffices to modify the respiratory behaviour. Structured light plethysmography (SLP) is a non-contact method of assessment of breathing pattern during tidal breathing. Firstly, we validated the SLP measurements by comparing timing component of the ventilatory pattern obtained by SLP versus PNT under the same condition; secondly, we compared SLP to SLP+PNT measurements of breathing pattern to evaluate the disruption of breathing pattern and breathing variability in healthy and COPD subjects. Measurements were taken during tidal breathing with SLP alone and SLP+PNT recording in 30 COPD and healthy subjects. Measurements included: respiratory frequency (Rf), inspiratory, expiratory and total breath time/duration (TI, TE and TT). Passing-Bablok regression analysis was used to evaluate the interchangeability of timing component of the ventilatory pattern (Rf, TI, TE and TT) between measurements performed under the following experimental conditions: SLP versus PNT, SLP+PNT versus SLP and SLP+PNT versus PNT. The variability of different ventilatory variables was assessed through their coefficients of variation (CVs). In healthy: Passing-Bablok regression proved high interchangeability of Rf, TI, TE and TT between measurements obtained under the three experimental conditions (SLP versus PNT, SLP+PNT versus SLP and SLP+PNT versus PNT). All the CVs describing "traditional" ventilatory variables (Rf, TI, TE, TI/TE and TI/TT) were significantly smaller in SLP+PNT condition. This was not the case for more "specific" SLP-derived variables. In COPD: Passing-Bablok regression proved high interchangeability of Rf, TI, TE and TT between measurements obtained under SLP versus PNT and SLP+PNT versus PNT and for Rf, TE and TT under SLP+PNT versus SLP. However, most discrete variables were significantly different between the SLP and SLP+PNT conditions and CVs were significantly lower when COPD patients were assessed in the SLP+PNT condition. Measuring ventilatory activity with SLP preserves resting tidal breathing variability, reduces instrumental observer effect and avoids any disruptions in breathing pattern induced by the use of PNT-mouthpiece-nose-clip combination.